Age‐Related Changes in FGF‐2, Fibroblast Growth Factor Receptors and β‐Catenin Expression in Human Mesenchyme‐Derived Progenitor Cells. Issue 3 (8th September 2015) - Hurley, Marja M.; Gronowicz, Gloria; Zhu, Li; Kuhn, Liisa T.; Rodner, Craig; Xiao, Liping
ABSTRACT: FGF‐2 stimulates preosteoblast replication, and knockout of the FGF‐2 gene in mice resulted in osteopenia with age, associated with decreased Wnt–β‐Catenin signaling. In addition, targeted expression of FGF‐2 in osteoblast progenitors increased bone mass in mice via Wnt‐β‐Catenin signaling. We posited that diminution of the intrinsic proliferative capacity of human mesenchyme‐derived progenitor cells (HMDPCs) with age is due in part to reduction in FGF‐2. To test this hypothesis HMDPCs from young (27–38), middle aged (47–56), and old (65–76) female human subjects were isolated from bone discarded after orthopedic procedures. HMDPCs cultures were mostly homogeneous with greater than 90% mesenchymal progenitor cells, determined by fluorescence‐activated cell sorting. There was a progressive decrease in FGF‐2 and FGFR1 mRNA and protein in HMDPCs with age. Since FGF‐2 activates β‐catenin, which can enhance bone formation, we also assessed its age‐related expression in HMDPCs. An age‐related decrease in total‐β‐Catenin mRNA and protein expression was observed. However there were increased levels of p‐β‐Catenin and decreased levels of activated‐β‐Catenin in old HMDSCs. FGF‐2 treatment increased FGFR1 and β‐Catenin protein, reduced the level of p‐β‐Catenin and increased activated‐β‐Catenin in aged HMDPCs. In conclusion, reduction in FGF‐2 expression could contribute to age‐related impaired function of HMDPCs via modulation of Wnt‐β‐catenin signaling. J. Cell. Biochem. 117: 721–729, 2016. © 2015 Wiley Periodicals, Inc.